KORELASI KREATIVITAS GURU DALAM MENGAJAR TERHADAP PRESTASI BELAJAR SISWA SDN 25 DOMPU - Mulya Yusnarti; Dedi Kusnadi (Universitas Borneo Tarakan, 2021)
Abstract: This study aims to determine the creativity of teachers in teaching learning achievement of students at SDN 25 Dompu. Data collection methods used were questionnaire and test. The data analysis technique used in this study is to use the Product Moment formula. Based on the results of data analysis that teacher creativity in teaching has a significant relationship with student achievement, this is indicated by the relationship of teacher creativity with student achievement from rxys count as big as 0.507 categories, teacher creativity contributes to student achievement by 25.70% and the remaining 74.30% is determined by other variables. It is proven that there is a significant relationship between teacher creativity and student learning achievement, it is calculated that 3.6733 is greater than the value of t-table 1.6828 or (3.6733 1.6828) according to the number of n = 41 At the 5% significance level or the 95% confidence level (table r product moment attached). This shows that the null hypothesis (Ho) which reads